Abdominal Pain and Vomiting due to Vertebral Artery Dissection: A Case Report of Stroke Chameleon. - Giannoni, Sara; Baldini, Mariella; Bartolozzi, Maria Letizia; Bertini, Elisabetta; Di Donato, Ilaria; Colon, Serena; Grifoni, Elisa; Madonia, Elisa; Signorini, Ira; Armellani, Massimo; et al. (Journal of Biomedical Practitioners, 2025)
INTRODUCTION The causes of nausea, vomiting, and abdominal pain can be multiple, sometimes including neurological conditions, especially if posterior cranial fossa structures are involved. CASE DESCRIPTION A 46-year-old man accesses the Emergency Department for sudden onset of algid sweating, headache, dizziness, vomiting, and severe abdominal pain. The diagnostic workup was negative for gastroenterological issues, and the patient was detained for observation. The following day, the patient developed right-sided Horner’s syndrome. MATERIALS AND METHODS Echo-color Doppler and neuro-radiological imaging of the cerebro-afferent vessels was performed with finding of right vertebral artery dissection. Brain magnetic resonance imaging (MRI) showed diffusion-restricted lesions in the right cerebellar hemisphere and dorsolateral medulla, indicative of ischemic stroke. RESULTS The patient progressively improved, and the neurological examination was normal at discharge. A six-month follow-up MR angiography of intra and extracranial vessels was performed, with persistent right vertebral artery occlusion, in the absence of wall hematoma or pseudoaneurysm. DISCUSSION Vertebral artery dissection is estimated to be the cause of approximately 2% of all ischemic strokes, with estimated annual incidence of 2.6-2.9 per 100,000 individuals. The events occur mostly in young individuals who typically present with non-specific symptoms such as dizziness, headache, and cervicalgia; therefore, onset associated with intense abdominal pain is extremely rare. CONCLUSION Recognizing that gastrointestinal symptoms may be, rarely, attributable to stroke is useful in avoid ineffective medical management and directing the correct diagnostic and therapeutic process.